2014
DOI: 10.1159/000357144
|View full text |Cite
|
Sign up to set email alerts
|

Early Pyeloplasty for Recovery of Parenchymal Thickness in Children with Unilateral Ureteropelvic Junction Obstruction

Abstract: Objective: We compared renal function before and after pyeloplasty in children with unilateral ureteropelvic junction obstruction (UPJO) according to the children's age. Methods: We reviewed the medical records of 36 children with UPJO who had undergone pyeloplasty and showed improved urine drainage on postoperative diuretic renal scan. The children were divided into two groups according to their age at the time of surgery: group I, ≤1 year of age (n = 15), and group II, >1 year of age (n = 21). Parenchymal th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 18 publications
2
7
0
Order By: Relevance
“…In another study, Kim and colleagues compared renal function before and after pyeloplasty in children with unilateral UPJO according to the children's age. They found surgical intervention before 1 year of age was a significant factor for recovery of PT [17]. Babu et al have shown that while renal function improves significantly in those undergoing early pyeloplasty, delayed surgery leads to marginal but significant loss of function.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Kim and colleagues compared renal function before and after pyeloplasty in children with unilateral UPJO according to the children's age. They found surgical intervention before 1 year of age was a significant factor for recovery of PT [17]. Babu et al have shown that while renal function improves significantly in those undergoing early pyeloplasty, delayed surgery leads to marginal but significant loss of function.…”
Section: Discussionmentioning
confidence: 99%
“…This question will remain a major challenge for the future. Actually, LP can duplicate the high success rates achieved with open pyeloplasty and within acceptable range duration, if performed by expert surgeons in centers with high laparoscopic expertise [26,27,28]. The LP procedure can be done through a transperitoneal approach or retroperitoneoscopically.…”
Section: Discussionmentioning
confidence: 99%
“…UPJO is a major cause of end-stage renal disease, which affects millions of children worldwide, highlighting the urgent need for early surgical intervention. However, the optimal timing and indications for surgical intervention in asymptomatic children with UPJO are controversial (2)(3)(4)(5)(6), given the possibility of spontaneous improvement in most hydronephrosis cases. Investigators have proposed intensive imaging protocols during the initial non-surgical management of patients, including serial ultrasound and diuretic renography (7,8).…”
Section: Introductionmentioning
confidence: 99%